2022
DOI: 10.3390/cells11162500
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Hydrogen Sulfide Modulates Dexamethasone-Induced Muscle Atrophy and Microvascular Rarefaction, through Inhibition of NOX4 and Induction of MGF, M2 Macrophages and Endothelial Progenitors

Abstract: Long-term use of Glucocorticoids produces skeletal muscle atrophy and microvascular rarefaction. Hydrogen sulfide (H2S) has a potential role in skeletal muscle regeneration. However, the mechanisms still need to be elucidated. This is the first study to explore the effect of Sodium hydrosulfide (NaHS) H2S donor, against Dexamethasone (Dex)-induced soleus muscle atrophy and microvascular rarefaction and on muscle endothelial progenitors and M2 macrophages. Rats received either; saline, Dex (0.6 mg/Kg/day), Dex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In agreement with these findings, different studies have observed that exogenous administration of H 2 S attenuates M1 polarization, including reduction of CD86 [ 24 ], CD11c [ 60 ], and iNOS [ 77 ] expression. H 2 S has also been indicated to lead to the polarization of macrophages from M1 to M2 phenotype [ 77 ], increasing the expression of M2 markers like CD206 [ 13 , 77 ] and CD163 [ 1 ]. In our study, GYY-4137 co-treatment failed to recover the reduction in gene expression of CD206 triggered by LPS, whereas protein levels were barely detected.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these findings, different studies have observed that exogenous administration of H 2 S attenuates M1 polarization, including reduction of CD86 [ 24 ], CD11c [ 60 ], and iNOS [ 77 ] expression. H 2 S has also been indicated to lead to the polarization of macrophages from M1 to M2 phenotype [ 77 ], increasing the expression of M2 markers like CD206 [ 13 , 77 ] and CD163 [ 1 ]. In our study, GYY-4137 co-treatment failed to recover the reduction in gene expression of CD206 triggered by LPS, whereas protein levels were barely detected.…”
Section: Discussionmentioning
confidence: 99%